Factors influencing juveniles' perception of the police in Karachi, Pakistan - Khoso, Abdullah; Khoso, Pasand Ali; Khushk, Ghulam Mujtab (Universiti Putra Malaysia Press, 2018)
The main objective of this study is to explore the role of juveniles' personal observation and their poverty status in influencing their perception of the police. The article draws on detailed informal interviews with 34 male juveniles on probation in Karachi. This study found that besides family members, friends and the media, juveniles' personal observation of the police's negative activities in their neighbourhood and vicinities was the leading factor influencing their perception of the police. All 34 juveniles have seen the police engaging in negative activities (being involved in crime) in their vicinity. In addition, the juveniles' poor socioeconomic status was found to be an important factor in shaping their negative perception although it was not as significant as the police's practice of criminalising the poor. It was also found that the majority of the juveniles were tortured; these juveniles claimed that they were innocent and were falsely implicated in false cases by the police. These vicarious encounters reinvigorated their pre-established negative perception of the police. The article concludes that personal observation plays a major role in shaping juveniles' perception of the police in Karachi.